Serological survey to toxoplasmosis in equids from two regions of Bahia State, Brazil - Mendonça, André de O.; Cerqueira, Eluzio José Lima; Araujo, Wildo Navegantes do; Silva, Evandro Moraes; Shimabukuro, Fábio Hiroto; Sarkis, Denise Tavares; Sherlock, Ítalo; Langoni, Helio (Semina: Ciências Agrárias, 2004)
It was studied the prevalence of Toxoplasma gondii infection in sera samples of equids from two regions of Bahia state. The indirect fluorescent antibody test (IFAT) and the modified agglutination test (MAD) were used to detect antibodies anti- T. gondii, taking as positive samples with titers equal or superior to 64. From 343 samples tested, five (1,5%) showed positive to both techniques. Statistically significant differences were not found regarding the species, sex, age, region and circulation ratio. The natural resistance of equids to toxoplasmic infection and the environmental conditions not favorable to the agent dissemination can explain the low prevalence of anti- T. gondii antibodies obtained in the present study.